EKSISTENSI KOMNAS HAM INDONESIA DALAM MENJALANKAN PERANNYA SEBAGAI UPAYA MENCARI KEADILAN SEHUBUNGAN DENGAN PELANGGARAN HAM - Suhardin Suhardin (Dinamika, 2021)
ABSTRACTThe National Commission on Human Rights or abbreviated as Komnas HAM Indonesia, this institution was established during the New Order era whose legal basis was established using Presidential Decree No. 50 of 1993. In the reform era, the existence of the National Human Rights Commission (Komnas HAM) was strengthened by the issuance of Law No. 39 of 1999 concerning Human Rights. However, the existence of Komnas HAM was doubted by the public for its independence because it was considered vulnerable to intervention by the government. 1. How is the development of human rights enforcement in Indonesia? 2. What are the obstacles for Komnas HAM in carrying out its role? 3. How does Komnas HAM handle cases of human rights violations in Indonesia? The research method in this research is normative juridical. The role of Komnas HAM in upholding human rights in Indonesia is very important to resolve cases of human rights violations and is needed in accordance with what is mandated by the Human Rights Law and in line with what the Indonesian people want. The Human Rights Law has weaknesses so that Komnas HAM cannot act proactively in carrying out its role. Komnas HAM in resolving cases of human rights violations is by means of reparation of the rights of the victims. Keywords: National Commission on Human Rights, Violations of Human Rights.ABSTRAKKomisi nasional hak asasi manusia atau disingkat Komnas HAM Indonesia, lembaga ini didirikan pada masa orde baru yang dasar hukum pembentukanya menggunakan Kepres No. 50 tahun 1993. Pada era reformasi keberadaan komisi nasional hak asasi manusia (Komnas HAM) diperkuat kedudukanya dengan lahirnya undang-undang No. 39 tahun 1999 tentang Hak Asasi Manusia. Namun keberadaan Komnas HAM sempat diragukan oleh publik atas indenpendensinya karena dianggap rentan di intervrensi oleh pemerintah.1.Bagaimana perkembangan penegakan HAM di Indonesia ? 2. Apa kendala dari Komnas HAM dalam menjalankan perannya ? 3. Bagaimana cara Komnas HAM dalam menangani kasus pelanggaran HAM di Indonesia ? Metode penelitian dalam penelitian ini adalah yuridis normatif. Peran Komnas HAM dalam penegakan HAM di Indonesia sangat penting untuk menyelesaikan kasus pelanggaran HAM dan dibutuhkan sesuai yang diamanatkan Undang-Undang HAM serta selaras denga apa yang diinginkan oleh masyarakat Indonesia. Undang-undang HAM memiliki kelemahan sehingga Komnas HAM tidak bisa bergerak secara pro aktif dalam menjalankan perannya. Komnas HAM dalam menyelesaikan kasus pelanggaran HAM yaitu dengan cara pemulihan (reparation) hak-hak korban. Kata Kunci : Komisi Nasional Hak Asasi Manusia, Pelanggaran Hak Asasi Manusia.